Prediction on Power Produced from Power Turbine as a Waste Heat Recovery Mechanism on Naturally Aspirated Spark Ignition Engine Using Artificial Neural Network - Herawan, Safarudin Gazali; Rohhaizan, Abdul Hakim; Ismail, Ahmad Faris; Shamsudin, Shamsul Anuar; Putra, Azma; Musthafah, Mohd Tahir; Awang, Ardika Ridal (Hindawi Publishing Corporation, 2016)
The waste heat from exhaust gases represents a significant amount of thermal energy, which has conventionally been used for combined heating and power applications. This paper explores the performance of a naturally aspirated spark ignition engine equipped with waste heat recovery mechanism (WHRM) in a sedan car.The amount of heat energy from exhaust is presented and the experimental test results suggest that the concept is thermodynamically feasible and could significantly enhance the system performance depending on the load applied to the engine. However, the existence of WHRM affects the performance of engine by slightly reducing the power.The simulation method is created using an artificial neural network (ANN) which predicts the power produced from theWHRM.